Dealing with the Coffee Crisis in Central America : Impacts and Strategies - Varangis, Panos (World Bank, Washington, DC, 2014)
Current coffee prices are at record lows and below the cost of production for many producers in Central America. Moreover, the coffee crisis is structural, and changes in supply and demand do not indicate a quick recovery of prices. So, coffee producers in Central America are facing new challenges-as are coffee laborers, coffee exporters, and others linked to the coffee sector. Coffee plays a major economic role in Costa Rica, El Salvador, Guatemala, Honduras, and Nicaragua. The coffee crisis is actually part of a broader rural crisis caused by weather shocks (such as Hurricane Mitch and droughts), low international agricultural commodity prices, and the global recession. These challenges call for new strategies for Central American countries aimed at broad-based sustainable development of their rural economies. The authors deal with the impact of the coffee crisis and strategies to deal with it. They include an analysis of the international coffee situation and country-specific analyses. The authors explore options and constraints for increased competitiveness and diversification, and discuss social, environmental, and institutional dimensions of the crisis. The authors conclude that there are specific solutions that can be pursued for the coffee sector. Some are already being applied, but more can be done in a more systematic way. Also, there is a need for safety nets to deal with the short-term impact of the crisis. Longer-term solutions are to be found in increased competitiveness and diversification in the context of broad-based sustainable rural economic development.